Entrepreneurship Intention of Students of the Faculty of Economics, Universitas Efarina Pematang Siantar - Ben Setiawan; Diana Florenta Butar-Butar; Suwita (International Journal of Economics (IJEC), 2022)
In study This there are 2 variables that is variable independent (X), and variable short (Y). Study This aim for test intention student in entrepreneurship at the Faculty of Economics at Efarina University ripening. Based on the total sample is 20 respondents, total sample made based on amount respondent that is as many as 20 respondents. In study This using the primary data obtained from deployment questionnaire. Amount distributed questionnaires as many as 20 copies and who can back and processed of 20 copies . From the results the can be concluded, development intention entrepreneurship in the faculty Efarina University of Economics is very influential in reduce level unemployed educated especially at efarina university.